2010
DOI: 10.1111/j.1600-051x.2010.01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical anchorage and peri‐implant bone formation of surface‐modified zirconia in minipigs

Abstract: It is concluded that all implants achieved osseointegration with similar degrees of BIC and BVD; however, titanium implants showed a higher resistance to removal torque, probably due to higher surface roughness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 28 publications
(31 reference statements)
3
65
2
2
Order By: Relevance
“…This result is in good agreement with previously published studies [11,12,21,25,26], in which the R a /S a value of the ceramics was slightly lower than the ones for Ti-SLA.…”
Section: In Vivo Studysupporting
confidence: 83%
See 3 more Smart Citations
“…This result is in good agreement with previously published studies [11,12,21,25,26], in which the R a /S a value of the ceramics was slightly lower than the ones for Ti-SLA.…”
Section: In Vivo Studysupporting
confidence: 83%
“…Consequently, a moderate surface roughness (in this case R a ~ 1.7 μm) significantly improves the rate of bone apposition (p ≤ 0.001). This finding is in good agreement with earlier studies on sandblasted zirconia ceramics [11,12], zirconia ceramics roughened via an additive surface treatment [21][22][23] and titanium surfaces with a graded roughness as reviewed in [10,24].…”
Section: In Vivo Studysupporting
confidence: 82%
See 2 more Smart Citations
“…Recently, zirconia has drawn attention as a new alternative to titanium as an implant material due to its superior biocompatibility and mechanical properties, including higher bending strength and fracture toughness. However, it has been reported that the osseointegration of zirconia implants is inferior to that of titanium implants, and there is no consensus at this time on the cell kinetics and osseointegration of zirconia implants [4][5][6][7] . In addition to osseointegration, other important issues must be taken into consideration with regard to implant materials such as their integration capabilities with soft tissues and anti-microbial properties in areas exposed to the mucosa.…”
Section: Introductionmentioning
confidence: 99%